Pengembangan Soal Numerasi Berorientasi AKM Berbasis Cagar Budaya Blitar untuk Kelas V Sekolah Dasar - Miftakhul Hanifa; Surayanah Surayanah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
The low availability of AKM-oriented numeracy items in elementary schools, as reflected in the results of PISA 2022, TIMSS 2023, and Rapor Pendidikan 2025, indicates the need to develop assessment instruments that are more contextual and relevant. This condition is reinforced by the results of needs questionnaires, interviews, and observations at SDN Kesamben 07 and SDN Kesamben 04, which showed that all 41 students stated that they needed an AKM-oriented numeracy assessment instrument. This study aims to develop AKM-oriented numeracy items based on Blitar cultural heritage for fifth-grade elementary school students that are valid, practical, and have good item quality. This study employed a research and development method using the Borg and Gall model implemented through 10 stages. The research subjects included 44 students at the preliminary trial stage, 41 students at the field trial stage, and 61 students at the operational field testing stage at SDN Kesamben 04, SDN Kesamben 07, and SDN Kesamben 06. Data were obtained through interviews, observations, questionnaires, item responses analyzed for each item, and documentation. The results showed that the product obtained a validity percentage of 95.31% in the very valid category, and instrument expert validation of 92.18% in the very valid category. Practicality according to teachers increased consistently across the three stages, with an average percentage of 96.25% in the very practical category, while practicality according to students reached an average percentage of 92.58% in the very practical category. The item analysis conducted in stages produced 29 final items that met all feasibility criteria. Thus, the 29 developed items have met the criteria of validity, practicality, and good item quality as a numeracy assessment instrument. This study contributes theoretically to the development of AKM numeracy assessment instruments and practically recommends the use of local culture-based assessments aligned with the Kurikulum Merdeka. In addition, this study opens opportunities for further studies on the effectiveness of the product at other educational levels and in different cultural heritage contexts.